Drilling - Samsuri, Ariffin (IntechOpen, 2018)
With regard to depleted oil and gas resources, increasing world energy demands and volatile economic and political world scenarios, oil and gas industry players are working very hard to find ways to cut exploration and production costs to sustain and develop the industry to provide the world with cheap energy without harming the environment. Therefore, this book intends to provide readers with a comprehensive overview of the current state of the art in drilling, such as advanced drilling operations and techniques used by the industry, particularly in floating, underbalanced drilling, smart drilling fluid, intelligent drilling, drilling optimization, and future drilling technology and development.